Da’wah Strategy Through Halal Tourism - Mahmuddin, Mahmuddin (Asian Journal of Social and Humanities, 2025)
This article focuses on the da’wah strategy of the Bulukumba Tourism, Youth, and Sports Office in developing halal tourism in Bulukumba, which is directed at the issue of the concept of the Bulukumba Tourism, Youth, and Sports Office in developing halal tourism in Bulukumba, the reasons for the Bulukumba Tourism, Youth, and Sports Office so that it is necessary to develop halal tourism in Bulukumba and the response of tourism managers and visitors to the development of halal tourism in Bulukumba. To obtain data in this study, the researcher used observation, documentation, interviews, and questionnaires. To obtain data related to visitor responses, the researcher used a grounded theory approach. The results of the study indicate that the concept of the Bulukumba Tourism, Youth, and Sports Office in developing halal tourism in Bulukumba, is halal hotels, halal restaurants, Islamic facilities, houses of worship, and Islamic entertainment. Meanwhile, the reason for the Bulukumba Tourism, Youth, and Sports Office to develop halal tourism in Bulukumba is to see the need to develop halal hotels, halal restaurants, Islamic facilities, houses of worship, and Islamic entertainment in order to develop halal tourism in Bulukumba. Regarding the response of tourism managers and visitors to the development of halal tourism in Bulukumba, the research results showed that visitors and tourism managers have high expectations for their positive response and have generally implemented the concept of halal tourism. Although there have not been full appeals or orders from the government, they have implemented it well. However, there are still some who have not fully implemented these expectations. The implication of this research is that the Bulukumba Regency government, specifically the Bulukumba Tourism, Youth, and Sports Office, is expected to conduct outreach and involve tourism managers in formulating all matters related to halal tourism in Bulukumba